2021
DOI: 10.3389/feart.2021.811621
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Climate Response in the Phenology of Crops in Northeast China

Abstract: Crop phenology is the process of crop growth and yield formation, which is largely driven by climatic conditions. It is vital to investigate the shifts in crop phenological processes in response to climate variability. Previous studies often only explored the response of a single crop phenology to climate change, and lacked comparative studies on the climate response in different crop phenology. We intend to investigate the trends in phenological change of three typical crops (i.e., maize, rice and soybean) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The seasonal precipitation of wheat generally showed a small variation, while that of rice demonstrated a large variation, which was compensated with irrigation water. A previous study found that length of growth periods of the crops were positively correlated with accumulated precipitation and accumulated sunshine hours, which was consistent with the results of this study …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The seasonal precipitation of wheat generally showed a small variation, while that of rice demonstrated a large variation, which was compensated with irrigation water. A previous study found that length of growth periods of the crops were positively correlated with accumulated precipitation and accumulated sunshine hours, which was consistent with the results of this study …”
Section: Resultssupporting
confidence: 93%
“…A previous study found that length of growth periods of the crops were positively correlated with accumulated precipitation and accumulated sunshine hours, which was consistent with the results of this study. 35 At the same time, compared with Optim. Fert.…”
Section: Resultsmentioning
confidence: 99%
“…As the population grows, so does the demand for food that mainly from crop production (Xia et al 2023;Hatfield and Dold 2018). Since crop growth and development are highly impacted by the climate conditions during the growing season (Rizzo et al 2022;Xiao et al 2021), climate variability and change pose considerable threats and challenges to global food security under the background of global warming (Pörtner et al 2022;Wang et al 2020;Lobell et al 2011). Generally, extreme climate is more likely to affect crop production than seasonal mean climate changes over the same period (Fu et al 2023;Zhang et al 2018;Jin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2019) and Lv et al (2015) analyzed the fluctuation characteristics and future trends of grain yield in crops. Other studies have investigated the temporal and spatial variation of crop phenology and its response to climate change (Lin et al, 2017;Xiao et al, 2021) and even the impact of crop phenology on crop growth (Wang et al, 2020). However, few studies have focused on crop phenology to analyze the comprehensive effects of climate change and the phenological response on agricultural production.…”
Section: Introductionmentioning
confidence: 99%